Impact of transmural plastic stent on recurrence of pancreatic fluid collection after metal stent removal in disconnected pancreatic duct: a randomized controlled trial - Chavan, Radhika; Nabi, Zaheer; Lakhtakia, Sundeep; Gupta, Rajesh; Jahangeer, Basha; Talukdar, Rupjyoti; Singh, Aniruddha Pratap; Karyampudi, Arun; Yarlagadda, Raghavendra; Ramchandani, Mohan; Kalapala, Rakesh; Jagtap, Nitin; Reddy, Manohar; Tandan, Manu; Rao, Guduru Venkat; Reddy, Nageshwar D. (Endoscopy, 2022)
Background Disconnected pancreatic duct (DPD) after development of walled-off necrosis (WON) predisposes to recurrent (peri)pancreatic fluid collection (PFC). In this randomized controlled trial, we compared plastic stents with no plastic stent after removal of a large-caliber metal stent (LCMS) on incidence of recurrent PFCs in DPD.Methods Consecutive patients with WON who underwent endoscopic ultrasound (EUS)-guided drainage with LCMS between September 2017 and March 2020 were screened for eligibility. At LCMS removal (4 weeks after drainage), patients with DPD were randomized to plastic stent or no stent groups. The primary outcome was incidence of recurrent PFC at 3 months. Secondary outcomes were technical success of plastic stent deployment, adverse events, stent migration, and recurrence of PFC at 6 and 12 months.Results 236 patients with WON underwent EUS-guided drainage using LCMS, and 104 (males 94, median age 34 years (interquartile range [IQR] 26–44.7) with DPD were randomized into stenting (n = 52) and no-stenting (n = 52) groups. Plastic stent deployment was successful in 88.5 %. Migration occurred in 19.2 % at median follow-up of 8 months (IQR 2.5–12). Recurrent PFCs occurred in six patients at 3 months (stent n = 3, no stent n = 3). There was no significant difference in PFC recurrence between the two groups at 3, 6, and 12 months. Reintervention was required in seven patients with recurrent PFCs, with no significant difference between the two groups.Conclusion In patients with WON and DPD, deployment of plastic stents after LCMS removal did not reduce recurrence of PFC.